An Anion‐Exchange Membrane Fuel Cell Containing Only Abundant and Affordable Materials. Issue 4 (16th February 2021) - Biemolt, Jasper; Douglin, John C.; Singh, Ramesh K.; Davydova, Elena S.; Yan, Ning; Rothenberg, Gadi; Dekel, Dario R.
Abstract : Herein, a unique anion‐exchange membrane fuel cell (AEMFC) containing only affordable and abundant materials is presented: NiFe hydrogen oxidation reaction (HOR) and nitrogen‐doped carbon oxygen reduction reaction (ORR) electrocatalysts. AEMFCs are an attractive alternative to proton‐exchange membrane fuel cells. They can run under alkaline conditions, allowing the use of platinum group metal (PGM)‐free electrocatalysts. Yet, the same alkaline conditions incur an overpotential loss in ORR and also slow the HOR. This can be solved by using PGM electrodes, but then the original advantage disappears. In contrast, the fuel cell is free of both PGMs and critical raw materials (CRMs). Electrochemical studies confirmed that the catalysts are highly active in both HOR and ORR in an alkaline electrolyte. The morphology, composition, and chemical states of the electrocatalysts are characterized by different techniques, including scanning electron microscopy (SEM), transmission electron microscopy (TEM), X‐ray photoelectron spectroscopy (XPS), X‐ray diffraction (XRD), and electron energy loss spectroscopy (EELS). Then, the electrocatalysts' performance is tested in a fuel cell device. The cell gives a maximum power density of 56 mW cm −2 and a limiting current density of 220 mA cm −2 . These results are among the best CRM‐free anion‐exchange membrane fuel cells reported to date. Abstract : Any long‐term sustainable solution to the energy transition challenge will need fuel cells that avoid critical raw materials. Herein, such an option using only nickel, iron, carbon, and nitrogen is presented.